Circuit board manufacturing method

JP7639839B2Active Publication Date: 2025-03-05AJINOMOTO CO INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023024640
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-03-05
Estimated Expiration
2043-02-20

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、誘電正接が低く、スミア除去性に優れる絶縁層を有する回路基板の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639839000003
    Figure 0007639839000003
  • Figure 0007639839000004
    Figure 0007639839000004
  • Figure 0007639839000005
    Figure 0007639839000005
Patent Text Reader

Abstract

To provide a manufacturing method of a circuit board, having an insulation layer of which a dielectric dissipation factor is low and which has an excellent smear removal property.SOLUTION: A manufacturing method of a circuit board includes: a step of laminating a resin sheet 1 with a support body, containing a support body 2 that includes a first surface 2a and a second surface 2b, in which a front surface resistance ratio of the first surface is 1.0*1011 Ω / sq. or less, and which has a plastic film and an anti-static layer, and a resin composition layer 3 that is bonded to a second surface of the support body to a base material so that the resin composition layer is bonded to the base material; a step of hardening the resin composition layer and forming an insulation layer; a step of forming a hole to the support body and the insulation layer; a step of performing desmear processing; a step of peeling the support boy; and a step of forming a conductive layer onto the insulation layer, in this order.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a circuit board. [Background technology]

[0002] Circuit boards are widely used in various electronic devices, and there is a demand for finer and denser circuit wiring in order to reduce the size and improve the functionality of the electronic devices.

[0003] As a manufacturing technique for circuit boards, a manufacturing method using a build-up method in which insulating layers and conductor layers are alternately stacked on an inner layer board is known. In a manufacturing method using the build-up method, for example, as described in Patent Document 1, an insulating layer is formed by laminating a resin composition layer on an inner layer board using, for example, a resin sheet with a support containing a support and a resin composition layer, and thermally curing the resin composition layer. Next, the formed insulating layer is drilled to form a via hole, and smears (resin residues) inside the via hole are removed (desmear treatment). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-37957 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, from the viewpoint of further miniaturization of circuit wiring, insulating layers used in circuit boards are required to have a low dielectric tangent, as well as smear removal properties to ensure electrical conduction reliability.

[0006] However, the present inventors have found that lowering the dielectric loss tangent of the insulating layer leads to poor smear removal performance, that is, there is a trade-off between the dielectric loss tangent and the smear removal performance.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for manufacturing a circuit board having an insulating layer with a low dielectric tangent and excellent smear removal properties. [Means for solving the problem]

[0008] One method for removing smears inside via holes is to perform a dry desmear treatment, but as a result of intensive research by the present inventors, it has been found that if the dielectric tangent of the cured product (insulating layer) of the resin composition layer is low, static electricity is generated when performing the dry desmear treatment, and due to the effect of this static electricity, it becomes difficult to remove smears inside via holes even when the dry desmear treatment is performed. 11 The inventors have found that the above-mentioned problems can be solved by using a resin sheet with a support, the resin sheet including a support having a resistance of Ω / sq. or less, and have thus completed the present invention.

[0009] That is, the present invention includes the following. [1] (A) A substrate having a first surface and a second surface, the surface resistivity of the first surface being 1.0×10 11 a step of laminating a support-attached resin sheet, the support including a support having a surface roughness of Ω / sq. or less and a resin composition layer bonded to a second surface of the support, onto a substrate such that the resin composition layer is bonded to the substrate; (B) curing the resin composition layer to form an insulating layer; (C) forming holes in the support and the insulating layer; (D) a desmear process; (E) peeling off the support; and (G) forming a conductor layer on an insulating layer in this order. [2] The method for producing a circuit board according to [1], wherein step (D) comprises performing a dry desmear treatment. [3] The method for producing a circuit board according to [2], wherein a gas species in the dry desmear treatment includes any one of a gas containing a fluorine atom, N2, and O2. [4] The method for producing a circuit board according to any one of [1] to [3], wherein the top diameter of the hole formed in the step (C) is 100 μm or less. [5] The method for producing a circuit board according to any one of [1] to [4], wherein the support includes a plastic film. [6] The method for producing a circuit board according to [5], wherein the plastic film contains either polyethylene terephthalate or polyethylene naphthalate. [7] The method for producing a circuit board according to [5] or [6], wherein the plastic film contains polyethylene naphthalate. [8] On a plastic film with a surface resistivity of 1.0×10 11 The method for producing a circuit board according to any one of [5] to [7], further comprising an antistatic layer having a resistance of Ω / sq. or less. [9] The method for producing a circuit board according to any one of [1] to [8], wherein the insulating layer has a dielectric tangent of 0.005 or less.

[10] The method for producing a circuit board according to any one of [1] to [9], wherein the resin composition layer contains either an active ester-based curing agent or a radically polymerizable compound.

[11] Before forming a conductor layer on the insulating layer in step (G), The method for producing a circuit board according to any one of [1] to

[10] , further comprising: (F) a step of performing a roughening treatment on a surface of the insulating layer.

[12] A substrate having a first surface and a second surface, the first surface having a surface resistivity of 1.0×10 11 A resin sheet with a support, the resin sheet comprising a support having a resistivity of Ω / sq. or less and a resin composition layer bonded to a second surface of the support, the support comprising polyethylene naphthalate. Effect of the Invention

[0010] According to the present invention, it is possible to provide a method for producing a circuit board having an insulating layer with a low dielectric tangent and excellent smear removal properties. [Brief description of the drawings]

[0011] [Figure 1]FIG. 1 is a schematic cross-sectional view illustrating one example of a support-attached resin sheet according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view for illustrating one example of another embodiment of the support-attached resin sheet of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view for illustrating one example of another embodiment of the support-attached resin sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below with reference to the following embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0013] Before describing the method for producing a circuit board of the present invention in detail, a support-attached resin sheet used in the method for producing a circuit board of the present invention will be described.

[0014] [Resin sheet with support] The resin sheet with a support includes a support having a first surface and a second surface, and a resin composition layer bonded to the second surface of the support, and the surface resistivity of the first surface of the support is 1.0×10 11 Ω / sq. or less.

[0015] FIG. 1 shows a schematic cross-sectional view of an example of a resin sheet with a support. The resin sheet with a support 1 includes a support 2 having a first surface 2a and a second surface 2b, and a resin composition layer 3 bonded to the second surface 2b of the support 2. The second surface 2b of the support 2 is the outermost surface of the support 2 and represents the surface on the side bonded to the resin composition layer 3. The first surface 2a of the support 2 is the outermost surface on the opposite side to the first surface 2a in the thickness direction of the support 2. The resin composition layer 3 is in direct contact with the second surface 2b of the support 2, and no other layer is provided between the support 2 and the resin composition layer 3. In the example shown in FIG. 1, the support 2 has a multilayer structure including a plastic film 21 having the second surface 2b of the support 2 and an antistatic layer 22 having the first surface 2a of the support 2.

[0016] Thus, one embodiment of a support-attached resin sheet 1 has a support 2 including a plastic film 21 and an antistatic layer 22, and a resin composition layer 3 bonded to the plastic film 21, and the surface resistivity of the surface (first surface) 2a of the antistatic layer 22 is 1.0×10 11 Ω / sq. or less.

[0017] The surface resistivity of the first surface 2a of the support 2 (i.e., the surface resistivity of the surface of the antistatic layer 22) is 1.0×10 11 Ω / sq. or less, preferably 1.0×10 9 Ω / sq. or less, more preferably 1.0×10 7 Ω / sq. or less. There is no particular lower limit, but it is preferably 1.0×10 2 Ω / sq. or more, more preferably 1.0×10 3 Ω / sq. or more, more preferably 1.0×10 5Ω / sq. or more. As mentioned above, if the dielectric loss tangent of the cured resin composition layer 3 is low, static electricity is generated during dry desmearing, and the effect of this static electricity makes it difficult to remove smears inside holes such as via holes (not shown). By setting the surface resistivity of the first surface 2a of the support-attached resin sheet 1 within this range, the effect of static electricity is suppressed, so that even if static electricity is generated, it becomes possible to remove smears inside holes such as via holes. As a result, even if a cured resin composition layer with a low dielectric loss tangent is used, it becomes possible to improve smear removal. The surface resistivity can be measured by the method described in the examples described below.

[0018] From the viewpoint of obtaining the effects of the present invention remarkably, the surface resistivity of the second surface 2b of the support 2 is preferably 1.0×10 13 Ω / sq. or less, more preferably 1.0×10 11 Ω / sq. or less, more preferably 1.0×10 9 The lower limit is preferably 1.0×10 2 Ω / sq. or more, more preferably 1.0×10 4 Ω / sq. or more, more preferably 1.0×10 6 The surface resistivity can be measured by the method described in the examples below.

[0019] The support in the resin sheet with a support may include a release layer 23 between the resin composition layer 3 and the plastic film 21, as shown in FIG. 2. In this case, the support 2 has a multilayer structure including a release layer 23 having a second surface 2b, a plastic film 21, and an antistatic layer 22 having a first surface 2a. The support in the resin sheet with a support may be a support formed by laminating an antistatic layer 22, a plastic film 21, a conductive layer 24, and a release layer 23 in this order from the first surface 2a, as shown in FIG. 3. In this case, the support 2 has a multilayer structure including a release layer 23 having a second surface 2b, a conductive layer 24, a plastic film 21, and an antistatic layer 22 having a first surface 2a.

[0020] <Support> The resin sheet with a support has a support. The support preferably has a plastic film and an antistatic layer. The support may also have a release layer and a conductive layer, if necessary.

[0021] -Plastic film- The plastic film may be a film made of a plastic material. Examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, it is preferable to include either polyethylene terephthalate or polyethylene naphthalate, and it is more preferable to include polyethylene naphthalate or polyethylene terephthalate.

[0022] The plastic film may be a commercially available product, such as Lumirror (manufactured by Toray Industries, Inc.), Diafoil (manufactured by Mitsubishi Chemical Corporation), or Teonex (manufactured by Toyobo Co., Ltd.).

[0023] From the viewpoint of obtaining the effects of the present invention prominently, the thickness of the plastic film is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, and is preferably 8 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more.

[0024] -Antistatic layer, conductive layer- The antistatic layer and the conductive layer have the function of increasing the conductivity in order to suppress the effect of static electricity generated when dry etching (desmearing process) is performed to remove smears inside holes such as via holes, and are usually formed on the surface of a plastic film.

[0025] The antistatic layer and the conductive layer have a surface resistivity of 1.0×10 11 The material may contain an antistatic agent so that the resistivity is Ω / sq. or less. Examples of the antistatic agent include organic antistatic agents and inorganic antistatic agents.

[0026] Examples of organic antistatic agents include quaternary ammonium salt type cationic compounds, sulfonic group-containing anionic compounds, ether type nonionic surfactants, antistatic polymers, and the like.

[0027] Examples of quaternary ammonium salt type cationic polymer compounds include trimethyl lauryl ammonium methyl sulfate, ethyl dimethyl stearyl ammonium ethyl sulfate, ethyl dimethyl oleyl ammonium ethyl sulfate, ethyl dimethyl lauryl ammonium ethyl sulfate, ethyl dimethyl stearyl ammonium metasulfonium, and ethyl dimethyl lauryl ammonium metasulfonium.

[0028] Examples of the sulfone group-containing anion compound include alkylsulfonates, alkylbenzenesulfonates, and polystyrenesulfonates.

[0029] Examples of the ether-type nonionic surfactant include polyether ester amide, polyether amide imide, polyether ester, and nonylphenol ether ethylene oxide.

[0030] Examples of the antistatic polymer include polythiophene-based antistatic polymers, polyaniline-based antistatic polymers, polypyrrole-based antistatic polymers, polyacetylene-based antistatic polymers, polyphenylene sulfide-based antistatic polymers, etc. Commercially available antistatic polymers may be used, and examples of the commercially available antistatic polymers include "WS-52R" manufactured by Shin-Nakamura Chemical Co., Ltd.

[0031] Examples of inorganic antistatic agents include metals such as aluminum and copper; and oxides of these metals, with either aluminum or copper being preferred.

[0032] From the viewpoint of obtaining the effects of the present invention remarkably, the thickness of the antistatic layer is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more, and is preferably 5000 nm or less, more preferably 3000 nm or less, and even more preferably 1000 nm or less.

[0033] From the viewpoint of obtaining the effects of the present invention remarkably, the thickness of the conductive layer is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, and is preferably 1000 nm or less, more preferably 500 nm or less, and even more preferably 300 nm or less.

[0034] When the support-attached resin sheet has a conductive layer, the conductive layer may be made of the same material as the antistatic layer or may be made of a different material, and the conductive layer may have the same surface resistivity as the antistatic layer or may be made of a different material.

[0035] The antistatic layer and the conductive layer can be formed, for example, by applying a coating liquid containing the above-mentioned antistatic agent and a known resin such as a thermosetting resin, a photocurable resin, or a thermoplastic resin onto a plastic film. In addition, an inorganic antistatic agent can be used to form an antistatic layer or a conductive layer on a plastic film by, for example, a vapor deposition method, a sputtering method, an ion plating method, or the like, using a metal such as aluminum or copper.

[0036] -Release layer- When the supported resin sheet contains a release layer, the release layer may be an inorganic release layer or an organic release layer, with an organic release layer being preferred.

[0037] The inorganic release layer may be a metal layer or a metal foil formed by a method such as a vapor deposition method, a sputtering method, an ion plating method, etc. Examples of metals contained in the inorganic release layer include aluminum, zinc, lead, nickel, etc., and aluminum is preferred.

[0038] The organic release layer may suitably be a release layer containing one or more organic polymers such as a fluororesin, an alkyd resin, a silicone resin, a polyolefin resin, a polyvinyl alcohol resin, an acrylic resin, a polyester resin, a melamine resin, or a cellulose resin.

[0039] When the resin sheet with a support includes a release layer, from the viewpoint of easily peeling the support from the insulating layer, the thickness of the release layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more, and is preferably 20 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 3 μm or less, 2 μm or less, or 1 μm or less.

[0040] When a support having a release layer is used, a plastic film with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the plastic film with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The plastic film with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0041] When using a plastic film with a release layer, the overall thickness of the plastic film with a release layer is, from the viewpoint of obtaining the effects of the present invention significantly, preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, and is preferably 8 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more.

[0042] From the viewpoint of obtaining the effects of the present invention remarkably, the thickness of the support is preferably 12 μm or more, more preferably 18 μm or more, and even more preferably 25 μm or more, and is preferably 100 μm or less, more preferably 60 μm or less, and even more preferably 40 μm or less.

[0043] <Resin composition layer> The support-attached resin sheet has a resin composition layer. The insulating layer can be formed by thermally curing the resin composition layer. Usually, the insulating layer contains a cured product of the resin composition layer, and preferably contains only the cured product of the resin composition layer.

[0044] From the viewpoint of obtaining the effects of the present invention remarkably, the thickness of the resin composition layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less.

[0045] The components contained in the resin composition layer are preferably those whose cured product has sufficient hardness, low dielectric tangent, and insulating properties. Examples of the components contained in such a resin composition layer include (a) an active ester-based curing agent and (b) a radical polymerizable compound. The resin composition layer may further contain (c) an epoxy resin, (d) an inorganic filler, (e) a curing accelerator, (f) a curing agent (excluding those corresponding to the component (a)), (g) a thermal radical agent, (h) a thermoplastic resin, (i) an organic filler, and (j) other additives, as necessary.

[0046] In the present invention, unless otherwise specified, the content of each component in the resin composition layer is a value when the non-volatile components in the resin composition layer are 100 mass %, and the non-volatile components mean all non-volatile components in the resin composition layer excluding the solvent.

[0047] -(a) Active ester curing agent- In one embodiment, the resin composition layer contains (a) an active ester-based curing agent. The (a) active ester-based curing agent can usually form a bond by reacting with the (c) epoxy resin described below to cure the resin composition layer. The resin composition layer can usually obtain a cured product with excellent peel strength with plating by using the (a) component in combination with the (c). The (a) component may be used alone or in combination of two or more types.

[0048] As the (a) active ester curing agent, generally, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0049] Specifically, the component (a) may include dicyclopentadiene-type active ester curing agents, naphthalene-type active ester curing agents containing a naphthalene structure, active ester curing agents containing an acetylated product of phenol novolac, active ester curing agents containing a benzoylated product of phenol novolac, active ester curing agents which are acetylated products of phenol novolac, and active ester curing agents containing a styryl group and a naphthalene structure. As the dicyclopentadiene-type active ester curing agent, an active ester curing agent containing a dicyclopentadiene-type diphenol structure is preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0050] Among these, the component (a) is more preferably at least one selected from active ester curing agents containing a dicyclopentadiene-type diphenol structure and naphthalene-type active ester curing agents containing a naphthalene structure.

[0051] Commercially available products of component (a) include active ester curing agents containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation); naphthalene-type active ester curing agents containing a naphthalene structure, such as "HP-B-8151-62T", "EXB9416-70BK", "EXB-8100L-65T", "EXB-8150L-65T", "EXB-8150-65T", "HPC-8150-60T", "HPC-8150-62T" (manufactured by DIC Corporation), and "PC1300-02-65T" (manufactured by Air Water Corporation); and a phosphorus-containing active ester compound, such as "EXB9401" (manufactured by DIC Corporation). "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener containing an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener containing a benzoylated product of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener which is an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester-based hardeners which are benzoylated products of phenol novolac; "EXB-8500-65T" (manufactured by DIC Corporation); and "PC1300-02-65MA" (manufactured by Air Water Corporation) as an active ester-based hardener containing a styryl group and a naphthalene structure.

[0052] From the viewpoint of being able to reduce the dielectric tangent and obtaining a cured product with excellent peel strength, the active ester group equivalent of the component (a) is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of an active ester-based curing agent containing one equivalent of an active ester group.

[0053] The ratio of the amount of the (c) epoxy resin to the (a) active ester curing agent is preferably 0.01 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is preferably 5 or less, more preferably 3 or less, and even more preferably 2 or less, in terms of the ratio of [total number of active groups of the active ester curing agent] / [total number of epoxy groups of the epoxy resin]. Here, the "total number of epoxy groups of the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the (c) epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "total number of active groups of the active ester curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the (a) active ester curing agent present in the resin composition by the active ester group equivalent. By setting the ratio of the amount of the (c) epoxy resin to the (a) active ester curing agent within this range, it is possible to obtain the effects of the present invention remarkably.

[0054] From the viewpoint of obtaining the remarkable effect of the present invention, the content of the component (a) is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, and the upper limit is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0055] -(b) Radical polymerizable compound- As an embodiment of the resin composition layer, it contains a radical polymerizable compound (b). The radical polymerizable compound (b) as the component (b) does not include those corresponding to the above-mentioned component (a). The component (b) may be used alone or in combination of two or more kinds.

[0056] The type of the (b) radical polymerizable compound is not particularly limited as long as it has one or more (preferably two or more) radical polymerizable unsaturated groups in one molecule. The (b) radical polymerizable compound may be, for example, a resin having one or more radical polymerizable unsaturated groups selected from maleimide group, vinyl group, allyl group, styryl group, vinylphenyl group, acryloyl group, methacryloyl group, fumaroyl group, and maleoyl group. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, the (b) radical polymerizable compound is preferably one or more selected from maleimide resin, (meth)acrylic resin, and styryl resin, and more preferably maleimide resin.

[0057] There is no particular limitation on the type of maleimide resin, so long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups) in one molecule. Examples of maleimide resins include (1) maleimide resins having an aliphatic skeleton (preferably an aliphatic skeleton having 36 carbon atoms derived from dimer diamine), such as "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all manufactured by DigiCner Molecules), and "SLK6895-T90" (manufactured by Shin-Etsu Chemical Co., Ltd.); (2) maleimide resins having an indane skeleton, as described in the Japan Institute of Invention and Innovation Disclosure Technical Bulletin No. 2020-500211; and (3) maleimide resins having an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Daiwa Kasei Co., Ltd.), and "BMI-80" (manufactured by Keiai Kasei Co., Ltd.).

[0058] The (meth)acrylic resin is not particularly limited in type, and may be a monomer or oligomer, as long as it has one or more (preferably two or more) (meth)acryloyl groups in one molecule. Here, the term "(meth)acryloyl group" is a general term for acryloyl and methacryloyl groups. Examples of methacrylic resins include (meth)acrylate monomers, as well as (meth)acrylic resins such as "A-DOG" (manufactured by Shin-Nakamura Chemical Co., Ltd.), "DCP-A" (manufactured by Kyoeisha Chemical Co., Ltd.), "NPDGA", "FM-400", "R-687", "THE-330", "PET-30", and "DPHA" (all manufactured by Nippon Kayaku Co., Ltd.).

[0059] The styryl resin is not particularly limited in type, and may be a monomer or oligomer, as long as it has one or more (preferably two or more) styryl groups or vinylphenyl groups in one molecule. Examples of the styryl resin include styrene monomers, as well as styryl resins such as "OPE-2St", "OPE-2St 1200", and "OPE-2St 2200" (all manufactured by Mitsubishi Gas Chemical Company, Inc.).

[0060] From the viewpoint of obtaining a remarkable effect of the present invention, the content of the (b) component is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 10% by mass or more, or 20% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on 100% by mass of the non-volatile components in the resin composition layer.

[0061] -(c) Epoxy resin- The resin composition layer may contain an epoxy resin (c) as a component (c) in combination with the component (a). The epoxy resin (c) as the component (c) does not include those corresponding to the above-mentioned components (a) to (b). The component (c) may be used alone or in combination of two or more kinds.

[0062] Examples of (c) epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, glycidyl cyclohexane type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.

[0063] The resin composition layer preferably contains, as the component (c), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the epoxy resin (c) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0064] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition layer may contain only a liquid epoxy resin, only a solid epoxy resin, or a combination of a liquid epoxy resin and a solid epoxy resin as component (c), but from the viewpoint of significantly obtaining the effects of the present invention, it is preferable that the resin composition layer contains a combination of a liquid epoxy resin and a solid epoxy resin.

[0065] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0066] Preferred liquid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure, glycidyl cyclohexane type epoxy resins, and phenolphthalimidine type epoxy resins, with bisphenol A type epoxy resins and naphthalene type epoxy resins being more preferred.

[0067] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation. ); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation; "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd. These may be used alone or in combination of two or more types.

[0068] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups in one molecule is preferable, a solid epoxy resin having three or more epoxy groups in one molecule is more preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is even more preferable.

[0069] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and biphenyl type epoxy resin is more preferred.

[0070] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "NC3000L" manufactured by Nippon Kayaku Co., Ltd. Examples of epoxy resins include "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL6121" (biphenyl type epoxy resin), "YX4000H", "YX4000HK" (bixylenol type epoxy resin), and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; and "WHR-991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more.

[0071] When a liquid epoxy resin and a solid epoxy resin are used in combination as component (c), the ratio by mass (liquid epoxy resin:solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:0.3 to 1:10, and particularly preferably 1:0.5 to 1:5. When the ratio by mass of the liquid epoxy resin and the solid epoxy resin is within this range, the desired effects of the present invention can be significantly obtained.

[0072] The epoxy equivalent of the (c) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, a cured product having sufficient crosslink density of the cured product of the resin composition layer can be obtained. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0073] From the viewpoint of significantly achieving the desired effects of the present invention, the weight average molecular weight (Mw) of the component (c) is preferably 100 to 5000, more preferably 150 to 3000, and even more preferably 200 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0074] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, the content of the (c) component is preferably 3 mass% or more, more preferably 5 mass% or more, and even more preferably 8 mass% or more, and is preferably 25 mass% or less, more preferably 20 mass% or less, and particularly preferably 15 mass% or less, based on 100 mass% of the non-volatile components in the resin composition layer.

[0075] -(d) Inorganic filler- The resin composition layer may contain an inorganic filler (d) as the component (d). By containing the inorganic filler (d) in the resin composition layer, it is possible to obtain a cured product having a low dielectric tangent.

[0076] (d) The inorganic filler is contained in the resin composition layer in the form of particles. (d) An inorganic compound is used as the material of the inorganic filler. (d) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. (d) The inorganic filler may be used alone or in combination of two or more kinds in any ratio.

[0077] (d) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellfiers" and "MGH-005" manufactured by Taiheiyo Cement Corporation; and "Sferique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0078] (d) The average particle size of the inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.5 μm or less. (d) The lower limit of the average particle size of the inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. (d) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0079] (d) The specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 (d) The upper limit of the specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0080] (d) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.

[0081] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0082] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.

[0083] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition layer or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0084] (d) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0085] From the viewpoint of obtaining a cured product with a low dielectric tangent, the content of the (d) inorganic filler is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, and is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, based on 100% by mass of the non-volatile components in the resin composition layer.

[0086] -(e) Curing accelerator- The resin composition layer may contain a curing accelerator (e) in combination with the component (c). The curing accelerator (e) as the component (e) does not include those corresponding to the above-mentioned components (a) to (d). The curing accelerator (e) functions as a curing catalyst that accelerates the curing of the epoxy resin (c).

[0087] As the (e) curing accelerator, a compound that accelerates the curing of the epoxy resin can be used. Examples of such (e) curing accelerators include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. As the (e) curing accelerators, one type may be used alone, or two or more types may be used in combination.

[0088] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0089] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0090] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0091] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0092] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0093] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0094] In order to obtain the effects of the present invention more significantly, the content of the (e) curing accelerator is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, and is preferably 1.5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less.

[0095] <(f) Hardener> The resin composition layer may contain a (f) curing agent. The (f) curing agent as the (f) component does not include those corresponding to the above-mentioned (a) to (e) components. The (f) curing agent usually forms a bond by reacting with the (c) epoxy resin to cure the resin composition. Examples of the (f) curing agent include phenol-based curing agents, naphthol-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, and carbodiimide-based curing agents. The (f) curing agent may be used alone or in combination of two or more.

[0096] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable.

[0097] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", and "EXB-9500" manufactured by DIC Corporation.

[0098] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0099] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0100] Specific examples of carbodiimide-based curing agents include "V-03" and "V-07" manufactured by Nisshinbo Chemical Inc.

[0101] When the curing agent is contained as the (f) component, the ratio of the amount of the (c) epoxy resin to the (a) active ester curing agent and the (f) curing agent is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.3 to 1:3, and even more preferably 1:0.5 to 1:2, in terms of the ratio of [total number of epoxy groups in the (c) epoxy resin]:[total number of active groups in the (a) active ester curing agent and the (f) curing agent]. Here, the "total number of active groups in the (a) active ester curing agent and the (f) curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the active ester curing agent and the curing agent present in the resin composition layer by the active group equivalent. By setting the ratio of the amount of the (a) component, the (c) component, and the (f) component within such range, the effect of the present invention can be obtained remarkably.

[0102] When the curing agent is contained as the (f) component, the ratio of the amount of the (c) epoxy resin to all of the (f) curing agents is preferably in the range of 1:0.01 to 1:1, more preferably 1:0.03 to 1:0.5, and even more preferably 1:0.05 to 1:0.3, in terms of the ratio of [total number of epoxy groups in the (c) epoxy resin]:[total number of active groups in the (f) curing agent]. Here, the "total number of active groups in the (f) curing agent" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the (f) curing agent present in the resin composition layer by the active group equivalent. By setting the ratio of the amount of the (c) component to the (f) component within this range, the effects of the present invention can be obtained significantly.

[0103] From the viewpoint of significantly obtaining the desired effect of the present invention, the content of the (f) curing agent is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer. The upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0104] -(g) Thermal radical agent- The resin composition layer may contain a thermal radical agent (g) in combination with the component (b). The thermal radical agent (g) usually has a function of promoting crosslinking of the radically polymerizable unsaturated group in the component (b). The thermal radical agent (g) as the component (g) does not include those corresponding to the above-mentioned components (a) to (f). The thermal radical agent (g) may be used alone or in combination of two or more kinds.

[0105] (g) Examples of thermal radical agents include peroxides such as t-butylcumyl peroxide, t-butyl peroxyacetate, α,α'-di(t-butylperoxy)diisopropylbenzene, t-butyl peroxylaurate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneodecanoate, and t-butyl peroxybenzoate.

[0106] (g) Commercially available thermal radical agents include, for example, “Perbutyl C”, “Perbutyl D”, “Perbutyl A”, “Perbutyl P”, “Perbutyl L”, “Perbutyl O”, “Perbutyl ND”, “Perbutyl Z”, “Percumyl P”, and “Percumyl D”, manufactured by NOF Corporation.

[0107] From the viewpoint of significantly obtaining the desired effect of the present invention, the content of the (g) thermal radical agent is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.

[0108] -(h)Thermoplastic resin- The resin composition layer may contain a thermoplastic resin (h) as the component (h). The thermoplastic resin (h) as the component (h) does not include those corresponding to the above-mentioned components (a) to (g). The thermoplastic resin (h) may be used alone or in combination of two or more kinds.

[0109] (h) Examples of thermoplastic resins include phenoxy resins, polyimide resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone resins, and polyester resins.

[0110] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0111] Specific examples of polyimide resins include "PIAD100H" manufactured by Arakawa Chemical Industries, Ltd., "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0112] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0113] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0114] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0115] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0116] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0117] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0118] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0119] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.

[0120] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.

[0121] (h) The weight average molecular weight (Mw) of the thermoplastic resin is preferably greater than 5,000, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.

[0122] In order to obtain the effects of the present invention more significantly, the content of the (h) thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and particularly preferably 0.5% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less, and particularly preferably 3% by mass or less, based on 100% by mass of the non-volatile components in the resin composition layer.

[0123] -(i)Organic filler- The resin composition layer may contain an organic filler (i) as the component (i). The organic filler (i) as the component (i) does not include those corresponding to the above-mentioned components (a) to (h). As the organic filler (i), any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, and examples of the organic filler include rubber particles, polyamide fine particles, silicone particles, etc.

[0124] As the rubber particles, commercially available products may be used, for example, "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.

[0125] (i) From the viewpoint of obtaining the effects of the present invention prominently, the content of the organic filler is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, and is preferably 3% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1% by mass or less.

[0126] -(j) Other additives- The resin composition may further contain (j) other additives as an optional non-volatile component in combination with the above-mentioned (a) to (i) components. (j) other additives include, for example, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters; and hindered phenol-based antioxidants. Antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiator assistants such as tertiary amines; photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, and thioxanthones. (j) Other additives may be used alone or in combination of two or more.

[0127] <(k) Solvent> The resin composition layer may further contain a (k) solvent as an optional volatile component in combination with the non-volatile components such as the above-mentioned components (a) to (j). As the (k) solvent, an organic solvent is usually used. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methoxypropionate, and the like. Examples of the solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (k) The solvent may be used alone or in combination of two or more.

[0128] The amount of (k) solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, or it can be 0 mass%.

[0129] <Other layers> In one embodiment, the resin sheet with a support may further include other layers as necessary. Examples of such other layers include a protective film provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and the like to the surface of the resin composition layer and scratches.

[0130] <Method of manufacturing a resin sheet with a support> The resin sheet with a support can be produced, for example, by preparing a resin varnish by dissolving the components contained in the resin composition layer in a solvent, applying the resin varnish to a support on which an antistatic layer or the like has been formed in advance using a die coater or the like, and then drying the varnish to form a resin composition layer. The solvent may be one described above.

[0131] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 1 minute to 10 minutes.

[0132] The resin sheet with a support can be stored in a rolled form. When the resin sheet with a support has a protective film, it can be used by peeling off the protective film.

[0133] The cured product obtained by thermally curing the resin composition layer of the support-attached resin sheet of the present invention at 200° C. for 90 minutes has a low dielectric loss tangent. Therefore, when an insulating layer is formed from this cured product, an insulating layer with a low dielectric loss tangent can be obtained. The dielectric loss tangent of the cured product (insulating layer) of the resin composition layer is preferably 0.005 or less, more preferably 0.004 or less, and even more preferably 0.003 or less. The lower limit is not particularly limited, but may be 0.0001 or more. The dielectric loss tangent can be measured by the method described in the examples below.

[0134] The cured resin composition layer of the support-attached resin sheet of the present invention has a surface resistivity of 1.0×10 11 Since the smear removability is Ω / sq. or less, the cured product has excellent smear removability. The maximum smear length of the cured product is preferably less than 2 μm, more preferably 2 μm or less, and even more preferably 1.5 μm or less. The lower limit is not particularly limited, but may be 0.001 μm or more. The "maximum smear length" refers to the maximum length of the smear from the circumference of the bottom of the via to the center of the circle. The smear removability can be evaluated by measuring according to the method described in the examples below.

[0135] The cured product obtained by curing the resin composition layer of the support-attached resin sheet of the present invention at 100°C for 30 minutes and 170°C for 30 minutes can usually increase the peel strength between the plating. Therefore, when an insulating layer is formed from this cured product, an insulating layer with high peel strength between the plating conductor layer can be obtained. The peel strength between the insulating layer and the conductor layer is preferably 0.3 kgf / cm or more, more preferably 0.4 kgf / cm or more, and even more preferably 0.5 kgf / cm or more. The upper limit of the peel strength is not particularly limited, but can be, for example, 10.0 kgf / cm or less. The peel strength can be measured by the method described in the examples below.

[0136] [Circuit board manufacturing method] The method for producing a circuit board of the present invention comprises the steps of: (A) a substrate having a first surface and a second surface, the first surface having a surface resistivity of 1.0×10 11a step of laminating a support-attached resin sheet, the support including a support having a surface roughness of Ω / sq. or less and a resin composition layer bonded to a second surface of the support, onto a substrate such that the resin composition layer is bonded to the substrate; (B) a step of thermally curing the resin composition layer to form an insulating layer; (C) forming holes in the support and the insulating layer; (D) a desmear process; (E) peeling off the support; and (G) forming a conductor layer on the insulating layer, in this order.

[0137] Such a method for manufacturing a circuit board makes it possible to manufacture a circuit board having an insulating layer with a low dielectric tangent and excellent smear removal properties, and also makes it possible to manufacture a circuit board having an insulating layer that generally has excellent peel strength between the insulating layer and the plated conductor layer.

[0138] Furthermore, the method for producing a circuit board of the present invention may, if necessary, include the following step (F) after step (E) and before forming a conductor layer on the insulating layer in step (G). (F) A step of roughening the surface of the insulating layer.

[0139] <Process (A)> In step (A), a resin sheet with a support is prepared. Then, the resin sheet with the support and a substrate are laminated so that the resin composition layer in the resin sheet with the support is bonded to the substrate. The resin sheet with the support is as described above.

[0140] A plate-shaped substrate is usually used as the substrate. Hereinafter, this substrate may be referred to as an "inner layer substrate". As the inner layer substrate, for example, a member having a substrate such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, or a thermosetting polyphenylene ether substrate may be used. In addition, the substrate may have a patterned conductor layer (circuit) formed on one or both sides. An inner layer substrate including such a circuit may be referred to as an "inner layer circuit board". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be formed during the manufacture of a printed wiring board is also included in the "inner layer substrate".

[0141] The resin composition layer and the inner layer substrate can be laminated, for example, by thermocompression bonding the resin sheet with the support to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet with the support to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the resin sheet with the support via an elastic material such as heat-resistant rubber so that the resin sheet with the support can sufficiently follow the surface irregularities of the inner layer substrate, rather than directly pressing the thermocompression bonding member against the resin sheet with the support.

[0142] The lamination of the inner layer substrate and the resin sheet with the support may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0143] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0144] After lamination, the laminated resin sheet with the support may be smoothed under atmospheric pressure, for example, by pressing the support side with a thermocompression member. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0145] <Process (B)> In step (B), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition layer. The curing conditions of the resin composition layer are not particularly limited, and the conditions adopted when forming an insulating layer of a printed wiring board may be used. The resin composition layer may be cured by irradiation with active energy rays such as ultraviolet rays, but is usually thermally cured by heating.

[0146] The thermal curing conditions of the resin composition layer vary depending on the types of components contained in the resin composition layer, but in one embodiment, for example, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time can be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0147] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0148] <Process (C)> In step (C), holes are formed in the support and the insulating layer. Typically, via holes are formed to penetrate the insulating layer. The shape of the holes is not particularly limited, but is generally circular (approximately circular).

[0149] The opening diameter (top diameter) of the hole that can be formed by carrying out step (C) is preferably 100 μm or less, more preferably 90 μm or less, even more preferably 80 μm or less, 70 μm or less, and preferably 5 μm or more, more preferably 10 μm or more, more preferably 20 μm or more, 30 μm or more, 40 μm or more. Here, the opening diameter (top diameter) of the hole refers to the diameter of the opening of the hole on the surface of the insulating layer.

[0150] Methods for forming holes include irradiation with laser light, etching, mechanical drilling, etc. Among these, irradiation with laser light is preferred from the viewpoint of obtaining the effects of the present invention more prominently.

[0151] Examples of laser light sources that can be used to form holes include CO2 lasers (carbon dioxide lasers), UV-YAG lasers, UV lasers, YAG lasers, and excimer lasers.

[0152] In irradiating the laser light, the number of shots is preferably 5 or less, more preferably 3 or less, from the viewpoint of improving the workability of the holes. In order to set the number of shots within the above range, it is preferable to set the energy and pulse width of the laser to a certain value or more. The output of the laser is preferably 0.1 W or more, more preferably 0.3 W or more, and even more preferably 0.5 W or more, and preferably 30 W or less, more preferably 10 W or less, and even more preferably 5 W or less. In addition, the pulse width of the laser is preferably 1 μsec or more, more preferably 5 μsec or more, and even more preferably 10 μsec or more, and preferably 40 μsec or less, more preferably 35 μsec or less, and even more preferably 30 μsec or less.

[0153] The holes can be formed using a commercially available laser device. Examples of commercially available carbon dioxide gas laser devices include "LC-2E21B / 1C" manufactured by Hitachi Via Mechanics, "ML605GTWII" manufactured by Mitsubishi Electric, "605GTWIII(-P)" manufactured by Mitsubishi Electric, and a substrate drilling laser processing machine manufactured by Matsushita Welding Systems. Examples of UV-YAG laser devices include "LU-2L212 / M50L" manufactured by Via Mechanics.

[0154] <Process (D)> When holes are formed in the insulating layer in step (C), resin residues called smears may be generated in the holes. In step (D), a desmear treatment is performed to remove the smears in the holes of the insulating layer. In the present invention, the surface resistivity of the first surface of the support is 1.0×10 11 A resin sheet with a support having a dielectric constant of Ω / sq. or less is used. Therefore, even if the insulating layer has a low dielectric tangent, the generation of static electricity can be suppressed, resulting in excellent smear removal properties.

[0155] The desmear treatment in the step (D) is usually a dry desmear treatment.

[0156] An example of the dry desmear treatment is a desmear treatment using plasma. In the desmear treatment using plasma, a gas is introduced into a plasma generating device to generate plasma and the plasma is used to treat the insulating layer, thereby removing smears generated in the holes. There is no particular limitation on the method of generating plasma, and examples thereof include microwave plasma in which plasma is generated by microwaves, high frequency plasma using high frequency waves, atmospheric pressure plasma generated under atmospheric pressure, and vacuum plasma generated under vacuum, and vacuum plasma generated under vacuum is preferred.

[0157] The gas species (gas species to be turned into plasma) in the dry desmear treatment is not particularly limited as long as it can remove smears in holes, and it is preferable to use, for example, a gas containing fluorine atoms, or a gas containing either N2 or O2. Examples of the gas containing fluorine atoms include F2, CF4, C2F6, and SF6. In this case, in addition to the gas containing fluorine atoms, N2, or O2, other gases such as Ar may be included. Among them, from the viewpoint of improving smear removability, the gas species preferably contains a gas containing fluorine atoms, or either N2 or O2, more preferably a gas containing fluorine atoms and O2, and further preferably a mixed gas containing O2 and at least one of N2 and CF4, and particularly preferably a mixed gas containing O2 and CF4.

[0158] When a mixed gas is used as the gas species, the mixture ratio (gas containing either N2 or O2 / other gas: unit: sccm) is preferably 1 / 0.01 to 1 / 100, more preferably 1 / 0.5 to 1 / 10, and further preferably 1 / 1 to 1 / 5, from the viewpoint of improving smear removal properties.

[0159] The time for the dry desmear treatment is not particularly limited, but is preferably 30 seconds or more, more preferably 60 seconds or more, 90 seconds or more, or 120 seconds or more. The upper limit of the time for the dry desmear treatment is preferably 10 minutes or less, more preferably 5 minutes or less, from the viewpoint of easily realizing an insulating layer with a small surface roughness after the desmear treatment.

[0160] The dry desmear treatment can be carried out using a commercially available dry desmear treatment device. Among the commercially available dry desmear treatment devices, examples suitable for the manufacturing of circuit boards include a plasma dry etching device manufactured by Oxford Instruments, a microwave plasma device manufactured by Nissin, and an atmospheric pressure plasma etching device manufactured by Sekisui Chemical Co., Ltd.

[0161] In step (D), after the dry desmear treatment, a wet desmear treatment may be performed as necessary. The wet desmear treatment is the same as that in step (G) described later.

[0162] <Process (E)> After the step (D) is completed, the support is peeled off in the step (E). This makes it possible to obtain an insulating layer with a low dielectric tangent and suppressed residual smear in the holes. By carrying out the step (E), the surface of the insulating layer is exposed, and it becomes possible to form a conductor layer on the exposed surface. A known method can be used as a method for peeling off the support.

[0163] <Process (F)> The method for producing a circuit board of the present invention may include a step of roughening the surface of the insulating layer after step (E) and before forming a conductor layer on the insulating layer in step (G), if necessary. The procedure and conditions of the roughening treatment are not particularly limited. The roughening treatment in step (F) may be either a dry roughening treatment or a wet roughening treatment, but from the viewpoint of obtaining the effects of the present invention significantly, the wet roughening treatment is preferable. The dry roughening treatment is the same as the dry desmear treatment in step (D).

[0164] In the wet roughening treatment, for example, a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are carried out in this order to roughen the insulating layer.

[0165] Examples of the swelling liquid used in the wet roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0166] An example of an oxidizing agent used in the wet roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0167] The neutralizing solution used in the wet roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0168] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment may be preferably 500 nm or less, more preferably less than 200 nm, even more preferably 100 nm or less, and even more preferably less than 100 nm. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0169] <Process (G)> Step (G) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0170] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0171] The thickness of the conductor layer depends on the desired design of the circuit board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0172] The conductor layer is preferably formed on the insulating layer by dry plating or wet plating, and is preferably formed by wet plating. As the dry plating, known methods such as vapor deposition, sputtering, ion plating, etc. can be used. As the wet plating, a method of forming a conductor layer by combining electroless plating and electrolytic plating, a method of forming a plating resist with a reverse pattern to the conductor layer and forming the conductor layer only by electroless plating, etc. can be mentioned.

[0173] In the step (G), from the viewpoint of ease of production, it is preferable to form the conductive layer by a semi-additive method. An example of forming the conductive layer by a semi-additive method will be described below.

[0174] A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0175] In the method for producing a circuit board of the present invention, the formation of insulating layers and conductor layers through steps (A) to (G) may be repeated as necessary to produce a multi-layer circuit board. EXAMPLES

[0176] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature conditions, pressure conditions, and humidity conditions are room temperature (25°C), atmospheric pressure (1 atm), and 50% RH.

[0177] <Measurement of surface resistivity> The surface resistivity (Ω / sq.) of the first and second surfaces of the supports used in the examples and comparative examples was measured using a surface resistivity measuring device (ADCMT's digital ultra-high resistance / microammeter "5451" and ADVANTEST's resistivity chamber "R12704A").

[0178] <Preparation of antistatic coating agent> An antistatic coating agent was prepared by mixing 1 part of antistatic polymer ("WS-52R" manufactured by Shin-Nakamura Chemical Co., Ltd.), 2 parts of polyester resin ("Vinal MD-1200" manufactured by Toyobo Co., Ltd.), 2 parts of water-based urethane resin ("E-37" manufactured by Daiichi Kogyo Co., Ltd.), 50 parts of water, and 45 parts of isopropyl alcohol.

[0179] <Preparation Example 1: Preparation of Support A> A PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) having a release layer that was treated with a non-silicone release agent (Lintec Corporation, "AL-5") was prepared. An antistatic coating agent was uniformly applied to the surface of the PET film opposite to the surface that contacts the release layer so that the antistatic layer had a thickness of 300 nm, thereby producing a support A (approximately 38 μm thick) having a release layer, a plastic film, and an antistatic layer in that order. The surface resistivity of the release layer surface (second surface) of support A was 1.0×10 13 Ω / sq., and the surface resistivity of the antistatic layer surface (first surface) is 1.0×10 9 It was Ω / sq.

[0180] <Preparation Example 2: Preparation of Support B> An antistatic coating agent was uniformly applied to a PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) so that the antistatic layer had a thickness of 200 nm, and then a release treatment was performed using a non-silicone release agent (Lintec Corporation, "AL-5"). Furthermore, an antistatic coating agent was uniformly applied to the opposite surface so that the antistatic layer had a thickness of 200 nm, producing a support B (approximately 38 μm thick) having a release layer, an antistatic layer, a plastic film, and an antistatic layer in that order. The surface resistivity of the release layer surface (second surface) in support B was 1.0×10 8 Ω / sq., and the surface resistivity of the antistatic layer surface (first surface) is 1.0×10 9 It was Ω / sq.

[0181] <Preparation Example 3: Preparation of Support C> Aluminum was vapor-deposited onto a PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) to a thickness of 60 nm. The opposite surface was then subjected to a release treatment using a non-silicone release agent (Lintec Corporation, "AL-5") to produce a support C (approximately 38 μm thick) having a release layer, a plastic film, and an antistatic layer in that order. The surface resistivity of the release layer surface (second surface) of support C was 1.0×10 13 Ω / sq., and the surface resistivity of the antistatic layer surface (first surface) is 1.0×10 7 It was Ω / sq.

[0182] <Preparation Example 4: Preparation of Support D> Copper was vapor-deposited onto a PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) to a thickness of 120 nm. The opposite surface was then subjected to a release treatment using a non-silicone release agent (Lintec Corporation, "AL-5") to produce a support D (approximately 38 μm thick) having a release layer, a plastic film, and an antistatic layer in that order. The surface resistivity of the release layer surface (second surface) of support D was 1.0×10 13 Ω / sq., and the surface resistivity of the antistatic layer surface (first surface) is 1.0×10 6 It was Ω / sq.

[0183] <Preparation Example 5: Preparation of Support E> In Preparation Example 1, the PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) having a release layer treated with a non-silicone release agent (Lintec Corporation, "AL-5") was changed to a PEN film (Toyobo Co., Ltd., "Product name Teonex Q83", thickness 25 μm) having a release layer treated with a non-silicone release agent (Lintec Corporation, "AL-5"). Except for the above, support E was prepared in the same manner as in Preparation Example 1. The surface resistivity of the release layer surface (second surface) in support E was 1.0×10 13 Ω / sq., and the surface resistivity of the antistatic layer surface (first surface) is 1.0×10 9 It was Ω / sq.

[0184] <Preparation Example 6: Preparation of Support F> A PET film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm) having a release layer that was treated with a non-silicone release agent (Lintec Corporation, "AL-5") was used as support F. The surface resistivity of the release layer surface (second surface) in support F was 1.0 × 10 13 Ω / sq., and the surface resistivity of the surface (first surface) opposite to the surface in contact with the release layer of the PET film is 1.0×10 14 It was Ω / sq.

[0185] <Preparation Example 1: Preparation of Resin Composition 1> Eight parts of a naphthalene type epoxy resin ("HP4032SS" manufactured by DIC Corporation, epoxy equivalent approximately 144 g / eq.), 15 parts of a biphenyl type epoxy resin ("NC3000H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 290 g / eq.), and 5 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, MEK solution with a solid content of 30 mass %) were heated and dissolved in 20 parts of toluene and 20 parts of MEK with stirring. The resulting solution was cooled to room temperature, and then mixed with 42 parts of an active ester curing agent (DIC Corporation's "HP-B-8151-62T", active group equivalent 238 g / eq., toluene solution with solid content of 62% by mass), 4 parts of a triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", hydroxyl group equivalent approximately 151 g / eq., 2-methoxypropanol solution with solid content of 50%), and 1 part of a carbodiimide curing agent (Nisshinbo Chemical Corporation's "V-03", active group equivalent approximately 216 g / eq., solid content of 50%). A mixture of 6 parts of a curing accelerator (a toluene solution with a solid content of 10% of "1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd.) and 3 parts of an inorganic filler (spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm) surface-treated with an amine-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.)) and 1 part of core-shell type rubber particles ("Staphyloid AC3816N" manufactured by Aica Kogyo Co., Ltd.) was mixed and uniformly dispersed in a high-speed rotating mixer to obtain resin composition 1.

[0186] <Preparation Example 2: Preparation of Resin Composition 2> Biphenyl aralkyl type maleimide resin ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., maleimide group equivalent: 275 g / eq., MEK / toluene mixed solution with 70% non-volatile content) 60 parts, bismaleimide resin ("BMI1500" manufactured by Designer Molecules, maleimide group equivalent: approx. 752 g / eq.) 10 parts, modified oligophenylene ether resin ("OPE-2St" manufactured by Mitsubishi Gas Chemical Co., Ltd.) Resin composition 2 was obtained by mixing 10 parts of a bifunctional acrylate ("NK Ester A-DOG" manufactured by Shin-Nakamura Chemical Co., Ltd., molecular weight 326 g / eq.), 5 parts of a thermal radical generator ("Perbutyl D" manufactured by NOF Corporation), 120 parts of an inorganic filler (spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm) surface-treated with an amine-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), and 20 parts of toluene, and uniformly dispersing the mixture in a high-speed rotating mixer.

[0187] <Preparation Example 3: Preparation of Resin Composition 3> 20 parts of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent 189g / eq.), 40 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3000H", epoxy equivalent approximately 290g / eq.), 30 parts of phenoxy resin (Mitsubishi Chemical Corporation "YX7553BH30", MEK solution with 30% solids by mass) were dissolved in 30 parts of toluene and 30 parts of MEK with stirring. After cooling the resulting solution to room temperature, 100 parts of active ester type curing agent (DIC Corporation "HPC-8000-65T", active group equivalent 223g / eq., toluene solution with 65% solids by mass), 10 parts of triazine skeleton-containing phenol type curing agent (DIC Corporation "LA-1356", hydroxyl group equivalent approximately 146g / eq., MEK solution with 60% solids by mass), bismaleimide resin (Designer Resin composition 3 was obtained by mixing 6 parts of "BMI689" manufactured by Shikoku Chemical Industries, Inc. (maleimide group equivalent: approximately 345 g / eq.), 5 parts of a curing accelerator (MEK solution of "1B2PZ" manufactured by Shikoku Chemical Industries, Inc. with a solid content of 10%) and 280 parts of an inorganic filler (spherical silica ("SO-C2" manufactured by Admatechs, average particle size 0.5 μm) surface-treated with an amine-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.)) and uniformly dispersing the mixture in a high-speed rotating mixer.

[0188] <Measurement of dielectric tangent> The protective film was peeled off from the resin sheet prepared in the examples, and the resin composition layer was thermally cured by heating at 200°C for 90 minutes, and then the support was peeled off. The obtained cured product was cut into a test piece having a width of 2 mm and a length of 80 mm. The dielectric tangent of the test piece was measured at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C by a cavity resonance perturbation method using an "HP8362B" manufactured by Agilent Technologies. Measurements were performed on three test pieces, and the average value was calculated.

[0189] [Table 1] *In the table, the contents of components (a) to (i) are values ​​when the non-volatile components in the resin composition layer are taken as 100 mass %.

[0190] [Example 1] (1) Preparation of a resin sheet with a support The prepared resin composition 1 was uniformly applied onto the surface of the release layer of the support A so that the thickness of the resin composition layer after drying was 25 μm. Thereafter, the resin composition layer was formed on the release layer by drying at 70° C. to 95° C. for 3 minutes. Next, the rough surface of a polypropylene film (Oji F-Tex Co., Ltd. "Alphan MA-411", thickness 15 μm) was attached as a protective film to the surface of the resin composition layer that was not bonded to the release layer. This resulted in a resin sheet with a support having the support A (antistatic layer, plastic film, release layer), the resin composition layer, and the protective film in this order.

[0191] (2) Surface preparation for inner layer circuit boards Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic R1515A) with an inner layer circuit formed thereon were etched 0.5 μm using MEC CZ8201 to roughen the copper surface.

[0192] (3) Lamination of a resin sheet with a support (step (A)) The protective film was peeled off from the resin sheet 1 with the support to expose the resin composition layer. Using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd., 2-stage build-up laminator, CVP700), lamination was performed on both sides of the inner layer circuit board so that the resin composition layer was bonded to the inner layer circuit board. The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Next, heat pressing was performed at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0193] (4) Curing of the resin composition layer (step (B)) The laminated resin composition layer was cured at 130° C. for 30 minutes and then at 170° C. for 30 minutes to form an insulating layer.

[0194] (5) Formation of via holes (step (C)) Using a Via Mechanics CO2 laser processing machine (LC-2E21B / 1C), holes were drilled in the support and insulating layer under the conditions of a mask diameter of 1.60 mm, a focus offset value of 0.050, a pulse width of 25 μsec, a power of 0.66 W, an aperture of 13, a number of shots of 2, and burst mode, to form a via hole with a top diameter (diameter) of 50 μm on the insulating layer surface.

[0195] (6-1) Dry desmear treatment (step (D)) The inner layer circuit board on which the insulating layer was formed, including the support, was subjected to a dry desmear treatment for 5 minutes using a vacuum plasma etching device (100-E PLASMA SYSTEM manufactured by Tepla) under conditions of O2 / CF4 (mixed gas ratio) = 25 / 75 and a vacuum degree of 100 Pa. The inner layer circuit board after the dry desmear treatment is referred to as evaluation board A.

[0196] (7-1) Peeling off the support and forming a conductor layer (step (E) and step (G)) After peeling off the support of evaluation board A, it was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then in an electroless copper plating solution at 25°C for 20 minutes. Next, it was heated at 150°C for 30 minutes to perform an annealing treatment, and then an etching resist was formed and a pattern was formed by etching. Then, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 25 μm, and an annealing treatment was performed at 200°C for 60 minutes. The inner layer circuit board after the plating conductor layer was formed is called evaluation board B.

[0197] <Evaluation of smear removal at the bottom of via holes> After peeling off the support from evaluation substrate A, the periphery of the bottom of the via hole was observed with a scanning electron microscope (SEM). From the obtained image, the maximum smear length from the wall surface of the bottom of the via hole was measured and evaluated according to the following criteria. ○: Maximum smear length is less than 2 μm ×: Maximum smear length is 2 μm or more

[0198] <Measurement of peel strength of plated conductor layer> A 10 mm wide and 100 mm long cut was made in the conductor layer of evaluation board B, and one end of this cut was peeled off and held with a gripper (TSE Corporation, Autocom type testing machine AC-50C-SL). The load (kgf / cm) when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured.

[0199] [Example 2] In Example 1, after (6-1) dry desmear treatment, the following (6-2) wet desmear treatment and (7-2) formation of a conductor layer were carried out to produce an inner layer circuit board. Except for the above, an inner layer circuit board was produced in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0200] (6-2) Peeling off the support and wet desmearing treatment (step (E) and step (F)) (6-1) After obtaining evaluation substrate A by dry desmearing, the support was peeled off and the substrate was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 5 minutes, then in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 10 minutes, then in a neutralizing solution (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of sulfuric acid) at 40°C for 5 minutes, and then dried at 80°C for 15 minutes. The inner layer circuit substrate after this process is designated evaluation substrate C.

[0201] (7-2) Formation of Conductive Layer (Step (G)) The surface of the evaluation board C that had been subjected to the wet desmear treatment was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. Next, the board was heated at 150°C for 30 minutes to perform an annealing treatment, after which an etching resist was formed and a pattern was formed by etching. Then, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 25 μm, and an annealing treatment was performed at 200°C for 60 minutes. The inner layer circuit board after the conductor layer was formed is called evaluation board D.

[0202] <Evaluation of smear removal at the bottom of via holes> The periphery of the bottom of the via hole of evaluation substrate C was observed with a scanning electron microscope (SEM), and the maximum smear length from the wall surface of the bottom of the via hole was measured from the obtained image and evaluated according to the following criteria. ○: Maximum smear length is less than 2 μm ×: Maximum smear length is 2 μm or more

[0203] <Measurement of peel strength of plated conductor layer> A 10 mm wide and 100 mm long cut was made in the conductor layer of evaluation board D, and one end of this was peeled off and held with a gripping tool (TSE Corporation, Autocom type testing machine AC-50C-SL). The load (kgf / cm) when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured.

[0204] [Example 3] In Example 1, 1) (1) Resin composition 1 in the preparation of a resin sheet with a support is changed to resin composition 2, 2) (7-1) Formation of a conductor layer was changed to (7-3) Formation of a conductor layer as shown below. Except for the above, an inner layer circuit board was produced in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0205] (7-3) Peeling off the support and forming a conductor layer (step (E) and step (G)) After peeling off the support from evaluation board A, a 30 nm titanium layer and then a 300 nm copper layer were formed by sputtering (E-400S, Canon Anelva Corporation). After heating at 150°C for 30 minutes for annealing, an etching resist was formed and a pattern was formed by etching. Then, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 25 μm, and annealing was performed at 200°C for 60 minutes. The inner layer circuit board after the conductor layer was formed is referred to as evaluation board B.

[0206] [Example 4] In Example 1, (1) the support A in the preparation of the resin sheet with a support was changed to the support B. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0207] [Example 5] In Example 4, (1) Resin composition 1 in the preparation of a resin sheet with a support was changed to Resin composition 3. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 4, and the smear removability and peel strength were evaluated.

[0208] [Example 6] In Example 1, (1) the support A in the preparation of the resin sheet with a support was changed to the support C. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0209] [Example 7] In Example 3, (1) the support A in the preparation of the resin sheet with a support was changed to the support C. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 3, and the smear removability and peel strength were evaluated.

[0210] [Example 8] In Example 3, 1) (1) In the preparation of the resin sheet with a support, the support A is changed to the support D, 2) (1) Resin composition 2 in the preparation of a resin sheet with a support was changed to resin composition 1. Except for the above, an inner layer circuit board was produced in the same manner as in Example 3, and the smear removability and peel strength were evaluated.

[0211] [Example 9] In Example 1, (1) the support A in the preparation of the resin sheet with a support was changed to the support E. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0212] [Comparative Example 1] In Example 1, (1) the support A in the preparation of the resin sheet with a support was changed to the support F. Except for the above, an inner layer circuit board was prepared in the same manner as in Example 1, and the smear removability and peel strength were evaluated.

[0213] [Table 2] [Explanation of symbols]

[0214] 1 Resin sheet with support 2 Support 2a First surface of support 2b Second surface of the support 21 Plastic Film 22 Antistatic layer 23 Release layer 24 Conductive layer 3 Resin composition layer

Claims

1. (A) having a first surface and a second surface, the surface resistivity of the first surface being 1.0×10 11 A step of laminating a support-attached resin sheet including a support having a surface roughness of Ω / sq. or less and a resin composition layer bonded to a second surface of the support, onto a substrate such that the resin composition layer is bonded to the substrate; (B) curing the resin composition layer to form an insulating layer; (C) forming holes in the support and the insulating layer; (D) a desmearing process; (E) peeling off the support; and (G) forming a conductor layer on the insulating layer in this order.

2. The method for producing a circuit board according to claim 1 , wherein the step (D) comprises performing a dry desmear treatment.

3. The gas species in the dry desmear treatment are a gas containing fluorine atoms, N 2 and O 2 The method for manufacturing a circuit board according to claim 2 , further comprising any one of the steps of:

4. The method for producing a circuit board according to claim 1 , wherein the top diameter of the hole formed in step (C) is 100 μm or less.

5. The method for producing a circuit board according to claim 1 , wherein the support comprises a plastic film.

6. The method for producing a circuit board according to claim 5 , wherein the plastic film contains either polyethylene terephthalate or polyethylene naphthalate.

7. The method for producing a circuit board according to claim 5 , wherein the plastic film comprises polyethylene naphthalate.

8. On a plastic film, the surface resistivity is 1.0×10 11 6. The method of claim 5, further comprising: forming an antistatic layer having a surface area of ​​0.1 Ω / sq. or less.

9. The method for producing a circuit board according to claim 1 , wherein the insulating layer has a dielectric loss tangent of 0.005 or less.

10. The method for producing a circuit board according to claim 1 , wherein the resin composition layer contains either an active ester-based curing agent or a radically polymerizable compound.

11. Before forming a conductor layer on the insulating layer in step (G), The method for producing a circuit board according to claim 1 , further comprising the step of: (F) performing a roughening treatment on the surface of the insulating layer.

12. A film having a first surface and a second surface, the first surface having a surface resistivity of 1.0×10 11 A resin sheet with a support, comprising a support having a surface roughness of Ω / sq. or less and a resin composition layer bonded to a second surface of the support, the resin composition layer contains either an active ester-based curing agent or a radical polymerizable compound; the radical polymerizable compound contains one or more selected from a maleimide resin and a styryl resin; A resin sheet with a support, wherein the support comprises polyethylene naphthalate.

Citation Information

Patent Citations

  • Thermosetting resin composition, b-stage resin film and multilayer build-up substrate

    JP2008037957A

  • Method of manufacturing circuit board

    JP2015211085A

  • Laminate structure and printed wiring board

    JP2016139794A

  • Photosensitive resin laminate, and method for forming resist pattern

    JP2018169548A

  • Laminate structure, cured product, printed wiring board and electronic component

    JP2020166136A